Effect of vegetable waste and banana stump composition in casabo fertilizer on nitrogen and phosphorus concentration - Firda Ainun Nisah; Wahyudin Wahyudin; Neneng Winarsih; Putri Febriyani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Liquid organic fertilizer is a solution resulting from the decay of organic materials derived from plant waste that contains more than one element. In Karawang, precisely in Telagasari Village, is the village with the largest banana fruit producer in West Java. In the Karawang market, a lot of vegetable waste has yet to be utilized, so it only causes a bad smell which can eventually cause disease. And there is not much processing of chicken eggshells even though they have a lot of nutritional content. CASABO fertilizer is a liquid organic fertilizer made from variations in chicken eggshells, vegetables, and banana stump composition. This research aims to utilize waste and make it a useful fertilizer for plants. This type of research is quantitative research using research methods or field experiments. This study consisted of 6 variations in the composition of eggshells, vegetable scraps, and banana stump. All materials were mixed with EM-4 and sugar water in the fermentation process. The results showed that the amount of material used affected the value of nutrients: pH 7.59° in P3, moisture content 92.65 in P2, Nitrogen 0.18% in P5, and phosphorus 0.04 in P1 and P2. In P1, the C-organic nutrient content was 5.54%, the C/N ratio was 79, and the potassium nutrient content was 0.09%. Based on these results, it can be seen that variations in the composition of vegetables and banana roots affect the value of phosphorus concentration and nitrogen concentration in CASABO organic liquid fertilizer.